STUDI FIKIH KHILAFAH ATAS KEPEMIMPINAN KHALIFAH JEMAAT AHMADIYAH - Wibowo, Irham; Dwi Prasetya, Fiki Febrian (Muadalah : Jurnal Hukum, 2024)
The Ahmadiyya Congregation is an international Islamic organization founded in Qadian, India, in 1889 by Mirza Ghulam Ahmad. Until now, this organization has expanded to more than 200 countries, including Indonesia. The highest leadership in this organizational structure is held by the Khalīfatul Masih (Promised Successor) who is currently based in London, England. Meanwhile, in each country, this organization is led by a National Amir who acts as the Chairman of the Central Board. The caliphate system adopted by the Ahmadiyya Congregation is believed to be a continuation of the Khilafah 'alā Minhājin Nubuwwah, with the main characteristic of being apolitical. The question is, this organization prohibits the establishment of political parties or the formation of a state based on their version of the caliphate system. The caliphate model of the Ahmadiyya Congregation is interesting to study because it has similarities with the Papal system in the Vatican. The process of electing the caliph is carried out through deliberation and consensus, although historically this position continues to be held by the descendants of Mirza Ghulam Ahmad. Their organizational structure is very hierarchical, where every decision and instruction from the caliph must be obeyed. The caliph is considered a figure chosen by God through human intermediaries, so that his attitudes and behavior are used as examples in social, sharia, and worship aspects. Rejecting the teachings of the caliph in this context is seen as a form of understanding of religion. The Ahmadiyya Community believes that the institution of the Khalīfatul Masih will continue until the end of time.